2019
DOI: 10.1016/j.gaitpost.2018.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Rate of torque development is the primary contributor to quadriceps avoidance gait following total knee arthroplasty

Abstract: Background: Following rehabilitation for total knee arthroplasty, "quadriceps avoidance gait", defined by limited knee flexion angle excursion during walking, persists and contributes to poor long-term outcomes. Given the presence of several post-surgical impairments, identifying the contribution of multiple factors to knee flexion angle excursion is important to developing targeted interventions to improve recovery after total knee arthroplasty.Research Questions: Which outcomes continue to improve following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…These outcomes may suggest that patients with a history of knee surgery are more susceptible to neuromuscular fatigue. Given the association between the lack of quadriceps central activation and force‐generating capacity and poor lower extremity biomechanics [35, 36], clinicians may also need to consider the alterations in kinematics and kinetics during and after exercises when treating patients with ACLR or meniscus surgery. However, there were similar decline patterns in quadriceps PT during and after fatigue protocols amongst the groups.…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes may suggest that patients with a history of knee surgery are more susceptible to neuromuscular fatigue. Given the association between the lack of quadriceps central activation and force‐generating capacity and poor lower extremity biomechanics [35, 36], clinicians may also need to consider the alterations in kinematics and kinetics during and after exercises when treating patients with ACLR or meniscus surgery. However, there were similar decline patterns in quadriceps PT during and after fatigue protocols amongst the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Quadriceps peak torque was quantified as the single highest torque value recorded for each individual trial (Figure 1). Rate of torque development was calculated as the slope of the torque time curve from 0 to 100 ms and 100 to 200 ms (Figure 1) (12,20). Recent work has shown that there is strong correlation between RTD sampled at 100 and 2000 Hz for the investigated time phases of 0-100 ms and 100-200 ms (6).…”
Section: Methodsmentioning
confidence: 99%
“…While reductions in knee flexion angles are commonly reported in the surgical knee post-total knee arthroplasty (TKA) compared to healthy controls 51 , these reductions should be corrected given their potential detrimental effects to ipsilateral cartilage integrity over the long-term 52 , as well as their relationship with knee-related quality of life 53 . This past year, Kline et al reported that rate of quadriceps torque development was the primary contributor to quadriceps avoidance gait (quantified via knee flexion excursion) post-TKA; knee pain and rate of quadriceps torque development (combined R 2 ¼ 0.34) 54 . Conversely, peak isometric quadriceps torque was a non-significant predictor in the modelling.…”
Section: Osteoarthritis Andcartilagementioning
confidence: 99%